Exposure to welding fumes is associated with hypomethylation of the F2RL3 gene: a cardiovascular disease marker. Issue 12 (22nd September 2015) - Hossain, Mohammad B; Li, Huiqi; Hedmer, Maria; Tinnerberg, Håkan; Albin, Maria; Broberg, Karin
Abstract : Background: Welders are at risk for cardiovascular disease. Recent studies linked tobacco smoke exposure to hypomethylation of the F2RL3 (coagulation factor II (thrombin) receptor-like 3) gene, a marker for cardiovascular disease prognosis and mortality. However, whether welding fumes cause hypomethylation of F2RL3 remains unknown. Methods: We investigated 101 welders (median span of working as a welder: 7 years) and 127 unexposed controls (non-welders with no obvious exposure to respirable dust at work), age range 23–60 years, all currently non-smoking, in Sweden. The participants were interviewed about their work history, lifestyle factors and diseases. Personal sampling of respirable dust was performed for the welders. DNA methylation of F2RL3 in blood was assessed by pyrosequencing of four CpG sites, CpG_2 (corresponds to cg03636183) to CpG_5, in F2RL3 . Multivariable linear regression analysis was used to assess the association between exposure to welding fumes and F2RL3 methylation. Results: Welders had 2.6% lower methylation of CpG_5 than controls (p<0.001). Higher concentrations of measured respirable dust among the welders were associated with hypomethylation of CpG_2, CpG_4 and CpG_5 (β=−0.49 to −1.4, p<0.012); p<0.029 adjusted for age, previous smoking, passive smoking, education, current residence and respirator use. Increasing the number of years working as a welder was associated with hypomethylation of CpG_4 (linear regression analysis, β=−0.11, p=0.039, adjusted for previous smoking). Previous tobacco smokers had 1.5–4.7% (p<0.014) lower methylation of 3 of the 4 CpG sites in F2RL3 (CpG_2, CpG_4 and CpG_5) compared to never-smokers. A non-significant lower risk of cardiovascular disease with more methylation was observed for all CpG sites. Conclusions: Welding fumes exposure and previous smoking were associated with F2RL3 hypomethylation. This finding links low-to-moderate exposure to welding fumes to adverse effects on the cardiovascular system, and suggests a potential mechanistic pathway for this link, via epigenetic effects on F2RL3 expression.